Outbreak Of Nipah Encephalitis In Greater Faridpur District (Faridpur Medical College Journal, 2011)
Nipah viral encephalitis is one of the fatal re-emerging infections especially in southeast Asia. After its outbreak in Malaysia and Singapore; repeated outbreaks occurred at western part of Bangladesh especially in Faridpur region. Besides, sporadic attacks appear to occur in the country throughout the year. Here two Nipah outbreaks in greater Faridpur district in 2003 and 2004 are described along with brief review on transmission of the virus. Where the history of illness among patients are very much in favour of man to man transmission. Moreover the death of an intern doctor from Nipah encephalitis who was involved in managing such patients in Faridpur Medical College Hospital strongly suggests man to man transmission of this virus. So, aim of this review article to make the health personnel and general people be aware about man to man transmission of virus, so that they can adapt personal protection equipment (PPE) for their protection against this deadly disease. DOI: 10.3329/fmcj.v5i2.6825Faridpur Med. Coll. J. 2010;5(2):63-65